The Punchdrunk encyclopaedia - Machon, Josephine, 1979- (Routledge, 2019)
"The Punchdrunk Encyclopaedia is the definitive book on the company's work to date, marking eighteen years of Punchdrunk's existence. It provides the first full-scale, historical account of one of the world's foremost immersive theatre companies, drawn from unrivalled access to the collective memory and archives of their core creative team. The playful encyclopaedic format, much like a Punchdrunk masked show, invites readers to create their own journey through the ideas, aesthetics, contexts, and practices that underpin Punchdrunk's work. Interjections from Felix Barrett, Stephen Dobbie, Maxine Doyle, Peter Higgin, Beatrice Minns, Colin Nightingale, and Livi Vaughan, among others, fill out the picture with in-depth reflections. Charting Punchdrunk's rise from the fringe to the mainstream, this encyclopaedia records the founding principles and mission of the company, documenting its evolving creative process and operational structures. It has been compiled to be useful to scholars and students from a variety of backgrounds and disciplines, from secondary level through to doctoral research, and is intended for those with a fascination for theatre in general and immersive work in particular. But ultimately it is written for devout fans, in acknowledgement of their continued support and contribution to Punchdrunk's history"--